Catalytic Co-Pyrolysis of Palm Oil Empty Fruit Bunch and Coal into Liquid Oil - Sunarno, Sunarno; Sari, Ronna Puspita; Frimacia, Tifanny; Yenti, Silvia Reni; Utama, Panca Setia; Saputra, Edy (International Journal of Renewable Energy Development, 2022)
The decline in fossil fuel sources has prompted research into finding renewable fuels. One of environmentally friendly energy sources with high efficiency is by producing liquid oil from palm oil empty fruit bunch (EFB) and coal. Pre-treatment of empty fruit bunches using NaOH and various concentrations of H2O2, various ratios of EFB/coal, the ratio of CaO catalyst, chemical and physical characteristics were studied to produce the better liquid oil yield. The H2O2 concentrations are 0%, 1%, 2%, and 3%. The ratios of EFB/coal (R) are 0/100, 25/75, 50/50, and 75/25. The ratios of catalyst CaO/raw material are 0%, 3%, 6%, and 9%. It ran at 400 Â°C with 100 mL/min nitrogen gas flowing during one hour. The results showed that adding sodium hydroxide and hydrogen peroxide in the EFB pre-treatment increased the liquid oil yield. With an increase in the EFB/coal ratio, the liquid oil yield increased. Co-pyrolysis treated EFB and Coal with a ratio of 75:25 produced 32% liquid oil yield, but the liquid oil yield decreased to 19% with the addition of 9% CaO catalyst. However, the addition of CaO catalyst reduces the acidity and increases the calorific value of the liquid oil.